Effect of Factors Financial, Trust, Demography, and Lifestyle of Purchase Intention Property in Jabodetabek - Dewi Ratna Sari; Deny Rahardjo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Several factors in determining the purchase of property products are the company's efforts to provide products that include several factors for its target consumers. Property products that are currently developing with various population segments from several property project developers can maximize strategies in property marketing. This study aims to determine the effect of financial, trust, demographic, and lifestyle factors on interest in buying a property. The main instrument of data collection is a questionnaire which is measured by a Likert scale. The number of respondents in this study were 108 Jabodetabek respondents. The analytical method used is Structural Equation Modeling (SEM). The results showed that the above factors boosted interest in buying a property product in Jabodetabek.